Essays on the proposed monetary integration in the ECOWAS region - Eshun, Richard (University of the Witwatersrand, Johannesburg, 2024)
Monetary integration has been projected to increase trade relations among member countries and plays an important role when it comes to economic growth through the elimination of trade barriers, the promotion of free movement of people and goods and the introduction of common external tariff and integration of payment system and capital markets of member countries. Whiles monetary integration in ECOWAS has been given much interest in extant literature; relevant research gaps remain largely in areas such as the introduction of ex-post monetary integration. In specifics, where the salient OCA criteria is used to examine the economic benefits member countries intend to gain with ex-post introduction of the single currency. The thesis contributes to fill this gap by investigating the ex-post introduction of monetary integration in ECOWAS. Knowledge of this is extremely crucial to policymakers to understand whether monetary integration can thus promote intra-regional trade in the ECOWAS region. This thesis comprises of four self–contained empirical essays. Each essay investigates a relevant lacuna in extant literature by relying on several advanced econometric techniques. In the first empirical study, we examined the level of integration of exchange rates between the West African Monetary Zone and the West African Economic and Monetary Union countries using wavelet-based methods. Findings suggest low degrees of integration between the two blocs at higher frequencies, but the level of integration gradually becomes stronger as it navigates from the higher frequency (lower scale) to the lower frequency (higher scale). It implies that ex-ante convergence of exchange rates is difficult, however, in the long-time horizon, exchange rates convergence is possible. Evidence from the cross-correlation analysis depicts lead (lag) effects Essays on the proposed monetary integration in the ECOWAS region 2024 © Richard Eshun Page iii are time-varying and heterogeneous, showing no country’s exchange rates as leader or follower. Different currencies have the potential to lead or lag at varying scales. In the second empirical essay, we investigated whether the impact of stock market development on growth in the ECOWAS region is dependent on the level of institutional quality such as voice and accountability, political stability, rule of law, control of corruption, government effectiveness, and government regulatory control. Our evidence suggests that, when institutional quality index is used as the mediating variable, we are able to establish that stock market development and economic growth nexus is contingent on institutional quality. Thus, the quality of the development of the stock market is important for economic growth, where better institutional quality is potent in ensuring the effectiveness of stock exchanges in promoting growth. The results also demonstrate that low quality of institutions tends to distort the ability of foreign direct investment (FDI) and domestic credit to the private sector which is used in this study to proxy for financial development to have any positive significant effect on growth. When we disaggregated the institutional quality index into its various dimensions whiles we constructed a stock market development index, our evidence suggests that, stock market development has a positive and significant effect on growth when political stability is above the threshold level. We further realized that, when government effectiveness is the threshold variable, stock market development has a positive and significant relationship with growth below the threshold level whiles higher regulatory control has a negative effect on how stock market development influences growth. This indicates that too much government interference inhibit the development of stock market to have a substantial positive influence on growth. This corroborates the financial repression and financial liberalisation theory by McKinnon and Shaw (1973) which is tested in this study objective. We established that, below the threshold level of Essays on the proposed monetary integration in the ECOWAS region 2024 © Richard Eshun Page iv voice and accountability, rule of law, and control of corruption, economic growth is largely insensitive to stock market development. Our main conclusion drawn is that, when there are higher levels of institutional quality, it can promote growth in the ECOWAS region. In the third empirical essay, we departed from the conventional way of studies on the relationship between labor migration and economic growth by examining the nonlinearities in this relationship by using Shin et al. (2014) methodology. What emerged is that the evidence supports the salutary effect of labor migration on economic growth in the ECOWAS sub-region. The baseline Autoregressive Distributed Lag results show that a 1% increase in labor migration reduces GDP by 0.66% which is statistically significant whiles the Non-linear Autoregressive Distributed Lag results show that, an increase in labor migration reduces GDP by 0.16% and a decrease in labor migration, increases GDP by 1.36% albeit insignificant in the long run. The essay evidences asymmetry relationship in the labor migration and economic growth nexus in ECOWAS. A key implication that emanates from this essay is that, policy makers in the ECOWAS sub-region should institute pragmatic measures to reap the full benefits of migration. In the fourth and final essay, the study examined whether there is a homogeneous causal relationship between trade openness and economic growth in the ECOWAS region by employing the Granger causality test by Dumitrescu and Hurlin (2012). As a robustness check, the study used four separate lags to establish this and out of the four lags, three lags show that trade openness homogeneously cause economic growth in the ECOWAS region, however, there is evidence from all the lags that economic growth does not homogenously cause trade openness. The findings reported no bidirectional causality in each of the variables. We further test the resilience of growth on impulses from trade openness; the evidence suggests the effect of transmission of GDP on its own shocks was permanent. In the long term, it will proceed to have Essays on the proposed monetary integration in the ECOWAS region 2024 © Richard Eshun Page v a positive impact on the economy. Evidence from the Impulse Response Function (IRF) result also discovered permanent policy shock of foreign direct investment (FDI) with a positive influence on GDP in the long-term whiles the percentage of variance explained by own shock in the short term accounted for 81.16% and continue a downward trend until it ends with an average around 68.42% at the end of the 10th period. The Pooled Mean Group/autoregressive distributed lag results show that trade openness has a positive and significant effect on economic growth with coefficient of 0.834 (0.0470) with P-value reported in parenthesis which indicates that a 1% increase in trade openness would lead to a 0.83% increase in GDP growth. At the policy front, ECOWAS heads of state should provide more effervescent and effective trade policies that are responsive to changing the trading market landscape in the sub-region while engaging economic agents to improve on trade infrastructure development which has evincing health for trade and economic growth.
Doctoral thesis submitted in fulfillment of the requirements for the award of Doctor of Philosophy in the field of Economics and Finance at The Graduate School of Business Administration, Wits Business School University of the Witwatersrand, Johannesburg 2025
Keywords: Economic growth; Exchange rates; Convergence; Labor migration; Monetary integration; Stock market development; Trade openness; SDG-8: Decent work and economic growth